Identification of a shark sequence resembling the major histocompatibility complex class I alpha 3 domain. - Hashimoto, K (1992)
Elasmobranchs (sharks and rays) branched off from the vertebrate line leading to the mammals more than 400 million years ago. They do not exhibit acute allograft rejection, and so far no report has pointed to the presence of major histocompatibility complex (MHC) antigen-like molecules in elasmobranchs. Here we demonstrate the existence of a gene in the shark (Triakis scyllia) genome with a sequence that resembles the MHC class I alpha 3 domains of other vertebrates. Several amino acids considered to be important for the interaction of the T-cell coreceptor CD8 with the MHC class I alpha 3 domain are conserved in the shark sequence.